Buya Hamka and Al-Azhar's Interpretation: The Contribution of Progressive Islamic Education in Muhammadiyah - Lintang Faza Muqoddas; Dartim Dartim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Buya Hamka is figure Indonesian Muslim intellectuals who play a role important in update Islamic thought through Al-Azhar tafsir which interprets the Qur'an in an honest way contextual with consider reality social, cultural, and historical Indonesian society. With use method tahlili Mushafi patterned on adab ijtima'i, this interpretation make the Qur'an as source reflective and responsive preaching to dynamics of the times. Research This aim study the role of Buya Hamka and Al-Azhar's contribution to interpretation in development Muhammadiyah's progressive Islamic education through approach qualitative with analysis thematic, especially on the concept purification and renewal. Study results show that renewal and purification are two principles that are mutually exclusive complement, where tajdid push update understanding of Islam to be relevant with need social, while purification guard purity teachings main from practice religious that is not based on. With Thus, Al-Azhar's interpretation contribute significant in strengthen Muhammadiyah Islamic education that is rational, contextual, and transformative, in line with with Spirit preaching progressive Islamic socialism.